Characterization and Evaluation of the Cytotoxicity of Pregabalin Gels for Oral Application - Gabriela Monteiro Barbosa Xavier; Lindalva Maria de Meneses Costa Ferreira; Marcele Fonseca Passos; Ana Paula Drummond Rodrigues; Felipe Tuji de Castro Franco; Cecy Martins Silva; José Otávio Carréra Silva Júnior; Roseane Maria Ribeiro-Costa; Jesuína Lamartine Nogueira Araújo (MDPI AG, 2024)
The efficacy of pregabalin in pain treatment has led to the search for new formulations for its use through different routes of administration. This study aimed to prepare, characterize, and evaluate the cytotoxicity of pregabalin (PG) gels for topical application in the oral cavity. Solutions with three different concentrations of PG were prepared and added to a 1.0% carbopol gel base. Thermal analyses (TG and DSC) and FTIR were performed on the gel and pure pregabalin. Stability (preliminary and accelerated) and rheology studies were also conducted on the gels. Cytotoxicity was evaluated in human gingival fibroblasts in the following groups: WG (1.0% carbopol gel base), PG2G (2.0% pregabalin gel), PG5G (5.0% pregabalin gel), and PG10G (10% pregabalin gel). A transparent and homogeneous gel with a pH of 6 was obtained. The formulations showed stability, and the different drug concentrations did not influence the product's characteristics. None of the tested groups showed cytotoxicity for the analyzed cells. The pregabalin gels exhibited favorable and non-toxic characteristics for human gingival fibroblasts in vitro. Therefore, this product may be a promising therapeutic alternative for topical application in the oral mucosa.